Juridical Study of Administrative Violations in General Elections in Accordance with Bawaslu Regulation of the Republic of Indonesia No. 8 of 2022 - Clara Agustine Pradinata; Ivana Kurniawan; Michelle Abigail Suganda; Ferdiansyah Prawira (CV. Rayyan Dwi Bharata, 2023)
The purpose of this study is to find out how the Juridical Study of Administrative Violations in Elections According to the RI Bawaslu Regulation No. 8 of 2022 and what are the problems that are often encountered in resolving election administration violations in accordance with RI Bawaslu Regulation No. 8 of 2022, and how efforts are being made to overcome them. This study uses a normative juridical approach to analyze and interpret legal regulations related to the settlement of administrative violations. The results of the study stated that in handling election administration violations, Bawaslu has an important role. They carry out inspections, investigations, and collection of evidence regarding reported or detected administrative violations. Bawaslu also plays a role as a mediator in resolving disputes, provides administrative sanctions to perpetrators of violations, and monitors and supervises the conduct of elections. In resolving election administration violations, Bawaslu faces several problems such as limited resources, complexity of cases, and differences in the interpretation of rules.